2004
DOI: 10.1097/01.aog.0000136100.10818.d8
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Organ Prolapse in Older Women: Prevalence and Risk Factors

Abstract: Some degree of prolapse is nearly ubiquitous in older women, which should be considered in the development of clinically relevant definitions of prolapse. Risk factors for prolapse differed depending on the definition of prolapse used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
163
4
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(195 citation statements)
references
References 16 publications
12
163
4
9
Order By: Relevance
“…In this study, the most common type of UP was third degree which was also observed in other studies [8,15]. First-degree variety was the most common presentation in an Italian study [12], second degree in a Nigerian study [11], and fourth degree in a study done in USA [18].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In this study, the most common type of UP was third degree which was also observed in other studies [8,15]. First-degree variety was the most common presentation in an Italian study [12], second degree in a Nigerian study [11], and fourth degree in a study done in USA [18].…”
Section: Discussionsupporting
confidence: 86%
“…In a study done in USA, giving birth to larger babies had more than two times greater risk of prolapse [15].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the US approximately half of all women over the age of 50 years have been reported to complain of symptomatic prolapse. [1][2][3][4][5] The burden of disease is found to be even larger in less affluent societies, where childbearing starts earlier, parity is higher, and access to all health care including gynaecological surgery is limited. [6][7][8][9] In spite of the magnitude of the problem worldwide, the knowledge of the aetiology and natural history of POP remains incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…6 Pelvic organ prolapse can be associated with urinary as well as bowel dysfunction. The etiology of POP is complex, involving potential injury to the many ligaments, muscles, connective tissue and innervation of the pelvis.…”
mentioning
confidence: 99%